JSA dan IBPRP Berdasarkan Permen PUPR No. 10 Tahun 2021 pada Proyek Jembatan Ruas–Mangun Jaya– Bts. Kab. Muba/Bts. Kab. Mura–Muara Beliti - Dony, Wari; Fadilla, Muhammad Akbar (Jurnal Talenta Sipil, 2025)
Workplace hazards can occur when the work environment causes injury, illness, or death. This danger can originate from many aspects including equipment, hazardous materials, processing processes, and work procedures. One of the risks of occupational hazards that occurs in a job is a work accident. The purpose of this research is to determine the identification of hazards and prevention carried out on the Section - Mangun Jaya - Bts Bridge Project. Muba District/Bts. District Mura – Muara Beliti and to analyze JSA and IBPRP based on PUPR Ministerial Decree No. 10 of 2021 on the Section – Mangun Jaya – Bts Bridge Project. Muba District/Bts. District Mura – Muara Beliti. The method used in this research is descriptive qualitative, namely trying to explain the condition of the subject and explain the real conditions that exist in the field. The data collection techniques used in this research are literature study, observation and interviews. Research steps carried out using the IBPRP method. The research results show that the results of risk analysis based on JSA show that there are 5 K3 policies that are declared very important and 4 K3 policies that are declared important. The highest score is for the statement "The company plans an K3 policy that involves workers" with a score of 0.85 and the lowest score is for the statement "The company provides the necessary budget for K3 and is transparent" with a score of 0.68. The results of the IBPRP risk analysis showed that of the 37 total risks in all jobs, there were 7 major risks (18.9%), 30 moderate risks (81.1%), and no jobs with low risk levels. The control plan carried out in this research is to carry out control using technical engineering, administration and personal protective equipment (PPE). From the results of carrying out risk control, it was found that there were changes in the level of risk in all types of work, including that there was no longer a large level of risk, a moderate risk level of 8 risks (21.6%), and a low risk level of 29 risks (78.4%). %). So it can be concluded that good implementation of JSA and IBPRP in bridge projects can effectively reduce the level of risk and increase work safety.